Seeing You in Me and Me in You: Personal Identification in the Phases of Mentoring Relationships - Humberd, Beth K.; Rouse, Elizabeth D. (Academy of Management Review, 2016)
Identification is integral to mentoring relationships, yet we know relatively little about the process through which mentors and protégés identify with each other, how this mutual identification shifts through the phases of the mentoring relationship, and how identification impacts the quality of the relationship over time. In this article we integrate theories of the self, relationships, and relational mentoring to consider the role of identification in informal mentoring. Specifically, we theorize how the process of personal identification occurs in mentoring from the perspective of both the mentor and protégé and offer a model that demonstrates how shifts in identification relate to the quality of the relationship that develops over time. We conclude with a discussion of implications for research and theory in mentoring.